2005
DOI: 10.1093/humrep/dei397
|View full text |Cite
|
Sign up to set email alerts
|

Time to pregnancy as a function of male and female serum concentrations of 2,2′4,4′5,5′-hexachlorobiphenyl (CB-153) and 1,1-dichloro-2,2-bis (p-chlorophenyl)-ethylene (p,p′-DDE)

Abstract: The overall results of the present study create a somewhat ambiguous pattern, but give some support to the idea that dietary POP exposure might be harmful for couple fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 48 publications
5
35
0
Order By: Relevance
“…The question whether malarial fever could explain the results has unfortunately not been addressed. The environmental exposure levels in these studies are high compared to current levels of DDT and DDT-metabolites in populations of other parts of the world, where low-level DDT exposure has not been associated with reduced sperm counts or male infertility [45,46]. In any case it is , disturbing that low-level exposure to PCBcongeners apparently interferes with sperm cell motility and sperm chromatin integrity in humans--findings that are consistent with experimental studies [47].…”
Section: Occupational Hazardssupporting
confidence: 67%
“…The question whether malarial fever could explain the results has unfortunately not been addressed. The environmental exposure levels in these studies are high compared to current levels of DDT and DDT-metabolites in populations of other parts of the world, where low-level DDT exposure has not been associated with reduced sperm counts or male infertility [45,46]. In any case it is , disturbing that low-level exposure to PCBcongeners apparently interferes with sperm cell motility and sperm chromatin integrity in humans--findings that are consistent with experimental studies [47].…”
Section: Occupational Hazardssupporting
confidence: 67%
“…The observed reduction in litter size is a likely consequence of poor rearing because unpublished data from our laboratory revealed no differences in fetal number at embryonic day 18 when dams were administered 1 μmole/kg 7 PCB 126 similar to the current exposure model (data not shown). Studies in humans have shown conflicting effects of maternal PCB exposure on fecundity, and specifically time to pregnancy [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Daughters' probability of pregnancy fell by 32% per 10μg/L p,p'-DDT in maternal serum, but increased 16% per 10μg/L p,p'-DDE. Axmon et al (2006), in a big study of INUENDO, evaluating exposure to CB-153 (biphenyl) and p,p'-DDE found no effect on TTP of either male or female exposure in Sweden, Poland and Ukraine. In Greenland there seemed to be an association, but it was not possible to determine if it was due to CB-153 or p,p'-DDE.…”
Section: Pesticide Exposure and Health Related Issues In Male And Femmentioning
confidence: 96%
“…One found decreased fecundity related to exposure (Gerhard et al, 1999) and three of the studies indicated no significant association (Law et al, 2005;Axmon et al, 2006;Harley et al, 2008). Two studies examined DDE exposure in women undergoing IVF with contrary results (Jarrell et al, 1993;Younglai et al, 2002).…”
Section: Pesticides and Time To Pregnancymentioning
confidence: 99%